Scaphoid Non-Union Treated by Zaidemberg's Vascularized Bone Graft: About 30 Cases - Mohamed Ali Sbai; Mayssa El M'chirgui; Riadh Maalla; Adel Khorbi (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2016)
Introduction: Scaphoid fractures evolves in 10% of cases to nonunion. Untreated, it progresses to arthrosis of the wrist that may compromise the function of the hand. The recently described vascularized bone grafts have helped to expand the armamentarium of management of scaphoid nonunion. We wanted to verify those data by studying the results of Zaidemberg's graft made in our orthopedic department. Materials and methods: 30 scaphoid nonunion cases treated by a vascularized bone graft using Zaidemberg's procedure were studied retrospectively. The clinical criteria studied were: range of motion, the Mayo Wrist Score, the Quick Dash, and PWRE. The radiographs have controlled the consolidation and performed a full radiometry. Results: Our series is made up of young adults (average age 28 years), a male-dominated manual workers. The dominant side is attained in 60% of cas.57% of patients are smokers. The seniority of the nonunion was 4 years on average. Nonunion sat, according to Schernberg's classifi cation in zone 3 in 30% of cases. We had 50% in stage 2a and 30% in stage 2b according to Alnot's classifi cation. Fixation was realized by pins followed by immobilization during 6 weeks on average. We had a consolidation in all cases. The tobacco intoxication had a deleterious effect, a delayed union was observed in smokers' patients. Our patients had a Mayo Wrist Mean score 72%, a PRWE to 11% and a Quick DASH 10%. Analysis of radiometry showed an improvement of the analyzed parameters. Conclusion: Zaidemberg's graft is a reliable vascularized bone graft; it requires a learning curve, these results are better than inert transplants and Kuhlmann's graft, it is indicated in the old nonunion, stage 2 Alnot the "proximal pole necrosis and changing of the scaphoid shape".